Pengaruh Penilaian Kinerja dan Bonus terhadap Kinerja Karyawan PT Medlinx Asia Teknologi Jakarta - Johan Trihantoro (UniSadhuGuna Business School, 2019)
This assessment aims to understand: ( 1 ) influence the work on performance employees. ( 2 ) influence the bonuses on performance employees .( 3 ) impact assessment of work and the bonuses simultaneously on performance employees of pt medlinx asia technology Jakarta this research be considered in research survey , with instrument of the research .The research by the sample as many as 50 respondents .Technical the analysis used is the linear regression simple and multiple standard significant on 5 % .The research on standard significant found that: ( 1 ) work assessment influential positive and significant on performance employees of pt medlinx asia technology Jakarta of 4.576 ( 2 ) the bonuses influential positive and significantly to employee performance of 5.006 ( 3 ) work assessment and a bonus influential positive and significantly to employee performance of 38.533